MAKNA PESAN BUDAYA DALAM SENI PERTUNJUKAN MUSIK TRADISIONAL CALEMPONG DI DESA KUOK KABUPATEN KAMPAR - Muhammad Iqbal; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The performing arts is one of the values of cultural heritage especially in rural communities Kampar Kampar Kuok. In the performing arts calempong there are aspects that are rich in symbolic meaning represented from physical objects, musical instruments. The aim of the study is to determine the meaning of the symbolic situation, meaning the products of social interaction and meaning interpretation of the performing arts in culture in the village calempong Kampar Kuok.This study used qualitative methods to approach symbolic interaction. Informants in this study is calempong players, coaches studios, community and village leaders Kampar Kuok. Data was collected through observation, interview, and documentation.The results showed that the meaning of the symbolic situation in the art of calempong performances in the village of Kuok Kampar Regency consists of the main tools, musical instruments, calempong, drum, saluang, while the social object of performing arts calempong is non verbal perilkau in the form of movement and kronemik. The meaning of social interaction products of performing arts of calempong in the form of performing arts performances calempong good side players, public figures and spectators. Players interpret the performing arts have the art of cultural value. Kampar community leaders interpret the performing arts have the value of solidarity. While the interpreter interpreted the performing arts as a motivation, as well as feelings of pleasure and pride. The calempong player's open actions include the facial expressions of the calempong music player against the rhythm of the music and the attitude of the calempong players in performing the performing arts of calempong.